Cluster strategy and supply chain management: The road to competitiveness for emerging economies. Issue 5 (2nd July 2018) - Ikram, Amir; Su, Qin; Fiaz, Muhammad; Rehman, Ramiz Ur
Abstract : Purpose: The purpose of this paper is to highlight the characteristic role of specialized markets and traders in the internationalization of emerging economies by examining the linkages between supply chain management (SCM) and industrial clustering in China. Design/methodology/approach: Multi-method approach was employed as primary data were collected from a case study of Shaoxing textile cluster, and was supplemented with secondary data to triangulate the findings. The proposition that competitive advantages of industrial clusters facilitate effective SCM was explored. Findings: The authors reveal that China's cost advantage is manifested in the entire value chain. The provision of business friendly amenities as a result of synergetic benefits of vertical and horizontal integration of supply clusters promotes competitiveness of SMEs and region as a whole. Moreover, specialized markets and international traders found to play significant role in sustainable cluster development. Research limitations/implications: As with fieldwork and case studies, generalization should be drawn with care. Systematic synthesis of relevant case studies is recommended. Practical implications: The study endorses the construction of local supply chains and suggests implementation of cluster strategy by focusing on environment-specific execution of triple helix model. Originality/value: The article elaborates the linkages between cluster theory and SCM both within cluster and between interspersed clusters. It also explains how specialized markets and global players are enabling concentrated supply networks. The paper recommends extension of "Triple helix + 1 model" by making local community part of the underlying framework.